Clinical Experience with Insulin Detemir: Results from the Bangladesh Cohort of Global A1chieve Study (BIRDEM Medical Journal, 2013)
Objective: To present results from the Bangladesh cohort of the A1chieve study receiving insulin detemir (Levemir) ± oral anti diabetic drugs. Methods: Out of 1093 patients recruited from 49 sites in Bangladesh, 370 were initiated on insulin detemir (Levemir).Study visits were defined as baseline, interim (around 12 weeks from baseline) and final (around 24 weeks from baseline) visit. Results: Glycaemic control was poor in all the groups at baseline. In the entire cohort at 24 weeks, significant reductions from baseline were observed in mean HbA1c (from 10.0 % to 7.2%, p